The Oxford handbook of music psychology - Hallam, Susan; Cross, Ian; Thaut, Michael 1952-
The 2nd edition of the Oxford Handbook of Music Psychology updates the original landmark text, providing a comprehensive review of the latest developments in this fast growing area of research. With contributions from internationally recognized experts, it is an essential resource for students and researchers in psychology